TINDAK TUTUR DIREKTIF GURU DAN SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI SMP NEGERI 1 JAKEN KABUPATEN PATI - Lutfi, Muhammad (MSJ : Majority Science Journal, 2023)
This research is motivated by the desire of researchers to find out what types of directive speech acts are used by teachers in learning Indonesian at SMP N1 Jaken. This study focuses on the problem of directive speech acts. The objects in this study were the teachers and students of SMP N 1 Jaken. the data in this study are teacher and student directive speech acts in Indonesian language learning at SMP N 1 Jaken. the method used in collecting data is the method of observing, noting, recording. Researchers are not involved in the learning interaction process. The researcher only listens, then uses the matching method to match the dialogue according to the type, function, and effect of speech. After that the researcher describes it with descriptive qualitative. The instrument in this study was the researcher himself. From this research, it can be concluded that the directive speech that is often used by the teacher is to order. The type of directive speech used is direct speech with imperative mode, the effect that is generated is a positive encouraging effect.